Pemahaman Mahasiswa Terhadap Objek Matematika : Kasus Pada Teori Grup - Dyah Ratri Aryuna; Ponco Sujatmiko (Delta: Jurnal Ilmiah Pendidikan Matematika, 2023)
The aim of this research is to describe students' understanding of the objects studied in group theory, namely objects that have meaning in a context and objects that have no meaning. Understanding objects in group theory is very important because it is an initial requirement for further study of group theory. This research is qualitative research. The subjects in this research were two students in the fourth semester of the Mathematics Education Study Program, FKIP UNS. Data was obtained from observations in lectures, lecture notes and written test results. The results of the research show that students' understanding of mathematical objects that have meaning in a context and those that do not have meaning tends to be relational understanding. Subjects can determine the outcome of a problem and can also explain the reasons for the answer. This can be seen from what students do, namely: (i). Mention one member of the set to show that the set is non-empty with an illustration, (ii). Claiming one of the members of the set is an and testing it using the definition of an identity element, (iii). Examining one by one or any member of the set and claiming the inverse element by testing it using the inverse definition